(untitled) (World Science, 2021)
The article presents the results of studying five varieties of quinoa in the conditions of the Southern Aral Sea region, which is very different from other agricultural zones in Uzbekistan by the lack of irrigation water and different soil salinity. It was revealed that quinoa varieties grow well in moderately saline soil and climatic conditions of the zone and form yields close to such conditions. The highest productivity indices were formed by varieties Ames 13761 (Q3) and NSL 106398 (Q5). The application of mineral fertilizers contributed to the accumulation of a higher yield. A cost-effective option for using mineral fertilizers is considered to be the N180P80K60 rate. Further increases in fertilizer rates do not cover the cost of increasing yields of quinoa varieties.